Pakistan : 2013 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper highlights Pakistan's 2013 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility. Discussions in the IMF report focus on macroeconomic policies to address vulnerabilities and reforms to promote robust inclusive growth. The authorities' ambitious economic program aims to reverse the current mix of large fiscal deficits and, accommodative monetary policy, and low reserve coverage, which provides few buffers to absorb shocks. The authorities have requested a 36-month extended arrangement under the Extended Fund Facility (EFF) for SDR 4.393 billion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet